Effectiveness of animated videos as information media on adolescent reproductive health in disaster situations - Widya Apriani; Yulia Fitri (Institute of Computer Science (IOCS), 2023)
Various efforts have been made in the field of reproductive health, especially in disaster situations. However, the distribution of available reproductive health services is still uneven, with limited access to services and a restricted understanding of reproductive health. This situation is further exacerbated by social and cultural barriers within the community. The primary objective of this research is to assess the efficacy of employing animated videos as an educational tool for enlightening adolescents about reproductive health amid disaster situations. The research design adopts a quasi-experimental approach utilizing a pretest-posttest group framework. A total of 40 participants were divided into two categories: the experimental group and the control group. The former was exposed to animated video content coupled with interactive discussions, while the latter adhered to conventional techniques involving PowerPoint presentations and lecture-style discussions. Prior to the dissemination of information, a preliminary test was conducted, followed by a subsequent test using identical questionnaires. Data analysis hinged on the T-test methodology. The outcomes of the study indicate that the utilization of animated videos notably amplifies adolescents' comprehension of reproductive health within disaster contexts (p = 0.043). Further research is imperative to delve into the efficacy of animated videos as informative instruments addressing health concerns within communities, encompassing a broader domain.